Building the managerial capital of agricultural cooperatives in Africa - Francesconi, Gian Nicola; Wouterse, Fleur Stephanie (John Wiley & Sons, 2019)
Agricultural cooperatives in Africa tend to be community‐based organizations defined by principles of inclusion, voluntarism, democracy, equity, autonomy, mutuality and solidarity. This means that they generally operate in accordance with the principles endorsed by the International Cooperative Alliance (ICA). However, only a few of these organizations are successful in commercializing the agricultural produce of their members. In this study, we argue that growth‐problems leading to commercial failure and organizational degeneration in these cooperatives can be attributed to a lack of managerial capital. Drawing on the literature and evidence from the field we set out key management solutions for counterbalancing cooperative principles in the context of rural Africa. These solutions were taught to the leaders and managers of 362 cooperatives at four training events held in Madagascar, Malawi and twice in Uganda. Using a production function for cognitive achievement and key informant interviews, we find that our training contributed to the adoption of the proposed solutions by some of the cooperatives. Using the Ugandan sub‐ sample, we estimate an OLS regression and a PSM model to show that the training translated into higher revenues per member generated through collective commercialization.